Bond Rating Change Announcement and the Effect on Stock and Bond Return - Pireningtyas, Fathia Hapsari; P., Umanto Eko (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
This research uses event study method in order to examine the difference in abnormal returns for stocks (average abnormal return) and bonds (spread yield). The sample used is listed companies in Indonesian Stock Exchange for the period 2007-2011 which issue corporate bonds and have bond rating changes issued by PT Pefindo. The analyses of this research were performed using one sample t test, paired t test, and multiple regression method. The results showed that: 1) There is no significant difference on average abnormal stock returns and abnormal bond returns before the announcement, during the announcement, and after the announcement of bond rating changes, 2) Cumulative return of stock increases following bond rating upgrades and decreases following bond rating downgrades although both are insignificant. In contrast, the cumulative return for bonds decreases significantly following bond rating upgrades and increases insignificantly following bond rating downgrade, and 3) The magnitude of bond rating changes gives no significant positive effect on average abnormal stock returns and spread yield.